New Forms of Government and the Europenisation of Minority Representation: the Case of European Roma - Anghel, Ionuţ Marian (European Journal of Social Science Education and Research, 2022)
The situation of roma since the fall of socialism is a paradox. On the one hand, many organizations, international governing organizations (IGOs), such as the European Union (Council of Europe, European Commission, European Parliament), the Organization for Security and Cooperation in Europe, the World Bank and the United Nations (UNDP, UNICEF, ILO), local and international/transnational NGOs, government agencies are involved in projects for Roma to improve their situation in Europe. Roma have become the target of social inclusion programs of the European Union (EU), the Decade of Roma Inclusion - a project of the Open Society Foundation and the World Bank -, Strategies for improving the situation of Roma developed by governments in Southeastern Europe. On the other hand, Roma continue to be marginalized, discriminated against, politically underrepresented, with a higher probability of being unemployed, not having access to public services - education, health , housing - compared with the majority population. This paper seeks to understand how was it possible to understand the recent shift from the representation of the Roma as a non-European minority, which lasted since their arrival in Europe until the fall of socialist regimes, to their representation as an European minority as it is shown in documents of the European institutions and the World Bank? How did Roma appear on the EU social inclusion agenda, the Human Development agenda of UNDP or the minority rights agenda of OSCE?
Keywords: roma, minority representation, governance